Additive Manufacturing Technologies and Applications - Carlo Giovanni Ferro (Ed.); Paolo Maggiore (Ed.); Salvatore Brischetto (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The present Special Issue proposes articles in the area of Additive Manufacturing with particular attention to the different employed technologies and the several possible applications. The main investigated technologies are the Selective Laser Sintering (SLS) and the Fused Deposition Modelling (FDM). These methodologies, combined with the Computer Aided Design (CAD), provide important advantages. Numerical, analytical and experimental knowledge and models are proposed to exploit the potential advantages given by 3D printing for the production of modern systems and structures in aerospace, mechanical, civil and biomedical engineering fields. The 11 selected papers propose different additive manufacturing methodologies and related applications and studies.